The Psycho-social and Health Effects of Illegal Immigration on immigrant Families Field Study Carried out on Families of Missing Illegal Immigrants in Ain El-Beida City, Oum El Bouaghi(Algeria). - amer, noura (Journal of Social Sciences and Humanities, 2021)
This research paper aims to shed light on the effects of illegal immigration on the members of the illegal immigrant’s family (mother, father, siblings – whom we could meet). So, this study employs the descriptive analytical method and applies a practical study on a purposive sample (08cases), depending on an interview with a group of illegal immigrants’ families. This study has been conducted in the city of Ain El-Beida, Oum El-Bouaghi and it has faced some difficulties, for instance, in meeting all the members and due to the ordeal the families are going through because they do not know anything about their sons whether they are dead or alive. For this reason, one of the main objectives of this study is to suggest solutions to reduce this negative phenomenon and its effects in the Algerian society. This study has found out that there are varying factors that drive the young to illegal immigration (harga) where the social conditions – rejection, marginalization, and the daily routine—come in the first place. Then comes the materialistic factor such as poverty, destitution, unemployment, and debt accumulation. After that comes the issues related to family like breakdown and the loss of one of the parents. Finally comes the temptation factor. This study has also underlined the main effects which can be stated as follows: the respondents of the sample agreed on the severe effects on the members of families that appear in the following order- from the most to the less negative-: the psychological (grief, depression, and hypochondria), the social and relational such as family breakdown, and the health problems such as psychosomatic illnesses and chronic diseases like diabetics and high blood pressure, Total Paralysis- Paraplegia and Migraines.